Predicting Mental Well-being Based on Personality Dimensions and Emotional Intelligence Mediated Treatment Adherencein Diabetic Patients - koushkestani, Atefeh; Sheybani, Hossein; Taher, Mahboobe (International Journal of Applied Behavioral Sciences, 2021)
Introduction: One of the biggest challenges of the 21st century for health systems around the world is the increasing burden of chronic diseases such as diabetes. Accordingly, the aim of the present study was to predict mental well-being based on personality dimensions and emotional intelligence mediated by adherence to treatment in diabetic patients.Methods: This research is a descriptive-correlational type, which has been analyzed using multivariate regression method. The statistical population of this study included all diabetic patients aged 30 to 60 years, who in the third quarter of the year 2019 referred to the office of endocrinologists, kidney and internal medicine specialist in 5 areas (north-south-center-east-west) of Tehran Municipality. Out of 714 people who referred to these centers, 267 people were selected as the sample by targeted sampling method and answered the Reef psychological well-being questionnaire, neo personality dimensions, shot emotional intelligence and following Modanlu treatment. SPSS software was used to analyze the statistical data. Results: The results of multivariate regression showed that 70% of the variance of psychological well-being in diabetic patients is explained by the variables of neuroticism, emotional intelligence, conscientiousness and extraversion, while the variables of openness to experience, pleasantness and adherence to psychotherapy did not have significant relation with psychological well-being.Conclusion: The results of this study, which are largely consistent with other research findings, indicate that high levels of emotional intelligence, conscientiousness and extraversion, and low levels of neuroticism increase the psychological well-being of diabetic patients.